Microwave-Assisted Copper-Catalyzed Coupling of Bromoalkynes and Sulfonamides: Rapid Synthesis of N-Sulfonyl Ynamides - Hong, Su Jeong; Lee, Joon-Ho; Yeom, Hyun-Suk (Synlett, 2023)
The synergistic effect of an alcohol solvent and microwave irradiation dramatically increased the C–N coupling rate, enabling the rapid synthesis of N-sulfonyl ynamides in ten minutes. The optimal catalyst, ligand, and solvent combination was investigated, and various bromoalkynes and sulfonamides were shown to be tolerated under these conditions.
Keywords: C–N coupling; ynamides; sulfonamides; microwave irradiation; solvent effect